Reframing Medical Malpractice Resolution: Restorative Justice between Indonesian Criminal Law and Iṣlāḥ in Contemporary Islamic Law - Hadi Purnomo; Widhi Handoko; Murad Altwaiqat (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
The enactment of Law Number 1 of 2023 on the Indonesian Criminal Code marks a shift in Indonesia’s criminal justice paradigm from retributive punishment toward restorative justice, emphasizing victim recovery, proportional accountability, and substantive justice. This transformation is particularly relevant to medical malpractice cases, which involve complex intersections of professional standards, medical ethics, and patient rights. Conventional punitive approaches have often failed to ensure victim restoration while risking excessive criminalization of medical practitioners. This study aims to analyze the application of restorative justice within the Indonesian criminal law system to resolve medical malpractice cases and to comparatively examine its conceptual convergence with the principle of iṣlāḥ in contemporary Islamic law, a peace-oriented dispute-resolution mechanism. This research employs a normative juridical approach by analyzing statutory regulations, legal doctrines, and contemporary Islamic legal scholarship related to restorative justice and iṣlāḥ. The analysis focuses on the philosophical foundations, normative structures, and practical implications of both legal frameworks. The findings reveal that the post-reform Indonesian Criminal Code provides a broader normative space for integrating restorative justice principles into criminal policy, including in the handling of medical malpractice disputes. Meanwhile, iṣlāḥ in contemporary Islamic legal thought emphasizes reconciliation, deliberation, proportional responsibility, and restoration of rights, grounded in Qur’anic values and Prophetic traditions. Comparatively, both frameworks demonstrate a shared restorative orientation that prioritizes balanced protection of victims and practitioners, social harmony, and sustainable conflict resolution, despite differences in epistemological foundations and normative sources. This study contributes to the development of an integrative restorative model by demonstrating the normative compatibility between Indonesian criminal law reform and Islamic legal principles, offering a more equitable, proportionate, and human-centered approach to resolving medical malpractice disputes in contemporary Indonesia.